Dexmedetomidine Combined With Patient-Controlled Analgesia for Palliative Sedation in Terminal-Stage Cancer Patients With Refractory Pain: A Retrospective Analysis of Nine Cases - Na Li; Yumei Wang; Meng Cui (Pain Research and Management)
Conclusion: DEX emerges as a promising option for palliative sedation in terminal-stage cancer patients. When used in conjunction with PCA, DEX has been shown to effectively, safely, and stably control refractory pain without inducing adverse effects such as respiratory/circulatory depression.